Metabolic associated fatty liver disease. A newproposal for a disease on the rise - Saavedra Chacón, María Fernanda; Pérez, Santiago; Guevara, Luis Gonzalo (Iatreia, 2021)
Nonalcoholic fatty liver disease is characterized by fat accumulation in the liver exceeding 5% of its weight. The spectrum of the disease includes fatty liver, steatohepatitis and progressive fibrosis leading to cirrhosis. It is also possible to develop hepatocellular carcinoma even without cirrhosis. Its physiopathology highlights the metabolic component of the disease, being acknowledged as a hepatic expression of a multisystemic metabolic disorder. Fat accumulation causes apoptosis, inflammation and fibrosis. In the view of the rising research on the subject, a new terminology is being proposed, consis-ting in metabolic associated fatty liver disease, now perceived as a standalone condition not needing the exclusion of other entities to make a diagnosis. The diagnosis includes the identification of liver steatosis and fibrosis, as a prognosis marker, using imaging studies and scoring models with biochemical markers. Treatment consists primarily in weight reduction and improving the metabolic baseline condition. New studies seeking pharmacologic interventions targeting hepatic inflammation are being conducted. Therapy also includes appropriate management of other medical comorbidities and cardiovascular risk control.